Assessing new prognostic biomarkers in resected colon cancer patients - Selven, Hallgeir (UiT The Arctic University of Norway, 2023)
Colon cancer is a common malignancy. We retrospectively established a biobank including 452 patients operated for colon cancer stage I-III in Northern Norway in the period 1998-2007. Tissue microarrays (TMAs) containing tumor tissue from these patients were constructed, and subsequently biomarker expression assessed by digital pathology. By using in situ hybridization, we assessed the expression of miR-126, miR-17-5p and miR-20a-5p. A high expression of all these miRs was related to improved disease-specific survival for these patients. For miR-17-5p and miR-20a-5p we investigated their functional aspects in select colon cancer cell lines. Over-expression of miR-17-5p and miR-20a-5p did not impact viability or invasion, and mitigated migration, strengthening our results of improved survival upon high expression. Additionally, using immunohistochemistry, we wanted to investigate four proteins thought to be regulated by these miRs; IRS-1, IRS-2, RUNX3 and SMAD4. In our material, a high expression of IRS-1, RUNX3 and SMAD4 was related to a favorable survival. These novel biomarkers could improve risk stratification in colon cancer patients, differentiating patients with a high risk of recurrence vs patients with a low risk of recurrence in the same TNM-stage. This could help the oncologists to choose the appropriate adjuvant treatment. For this to be implemented in clinical practice, the results need to be verified in large prospective trials.